Analysis Of Volleyball Basic Technical Skills In Extraculicular Activities - Muhammad Zamroni; Irsan Kahar; Suaib Nur (STKIP Muhammadiyah Kuningan, 2023)
This study aimed to determine the ability of basic volleyball techniques in MAS Wathaniyah Belopa's extracurricular activities. The type of research used is quantitative descriptive research. The sampling technique in this study used the total sampling technique with a total sample of 24 people. The data analysis used is descriptive, one of the quantitative data analysis techniques that aim to describe or provide an overview of the data. The results showed that the ability level of basic volleyball techniques in extracurricular activities at MAS Wathaniyah Belopa was based on the research results obtained from the results of the under-serve and over-serve in volleyball extracurricular activities at MAS Wathaniyah Belopa, out of 24 students who took the volleyball service test, the lower serve skill level dominates the medium category with a percentage of 50%. Then the upper serve skills dominated the less category by 41.7% of the 24 students who took the test. Underhand passing and upper passing skills in volleyball extracurricular activities at MAS Wathaniyah Belopa, of the 24 students who took the volleyball passing test, the level of lower passing skills dominated the medium category with a percentage of 50%. Then the top passing skills dominate the good category by 58.3%. Smash skills in volleyball extracurricular activities at MAS Wathaniyah Belopa showed that of the 24 students who took the volleyball smash test, the level of smash skills dominated the medium category with a large percentage of 41.7%. The basic technical skills of playing volleyball in MAS Wathaniyah Belopa's extracurricular activities are suitable.